Symptomatic hepatic metastasis of insulinoma 15 years after pancreatic resection - (:unkn) unknown (AVES, 2018)
Malignant insulinomas are infrequent endocrine tumors with miscellaneous clinical courses. In this report, we present a rare case of insulinoma that recurred with solitary hepatic metastasis 15 years after the initial resection of the primary tumor from the pancreas. A 20-year-old woman first presented with the symptoms of hypoglycemia in 1996. The diagnosis of pancreatic insulinoma was confirmed by laboratory findings, and the initial surgery had been performed involving complete enucleation of the pancreatic mass. Histopathologically, the tumor was diagnosed as a benign adenoma. After 15 years, the patient experienced symptoms of hypoglycemia again, and laboratory findings and abdominal computed tomography identified a lesion in the liver. Intraoperative ultrasound did not show any lesion in the pancreas, and wedge resection was performed for the hepatic lesion. Postoperative blood glucose levels returned to normal. Histopathologic examination confirmed the diagnosis of liver metastasis of a neuroendocrine tumor. This is the longest interval between primary tumor and the metastasis reported in the literature, for insulinoma. Thus, it should be remembered that long-term follow-up is mandatory for the patients with insulinoma even after resection of the primary tumor. Resection is recommended when a metastatic lesion is observed.
Keywords: Insulinoma; pancreas; liver; metastasis; MALIGNANT INSULINOMA; NEUROENDOCRINE TUMORS; ENDOCRINE TUMORS